President Johnson's war on poverty : rhetoric and history - Zarefsky, David (University, Ala. : University of Alabama Press, 1986)
Normal0falsefalsefalseMicrosoftInternetExplorer4 In January 1964, in his first State of the Union address, President Lyndon Johnson announced a declaration of "unconditional war" on poverty. By the end of the year the Economic Opportunity Act became law. The War on Poverty illustrates the interweaving of rhetorical and historical forces in shaping public policy. Zarefsky suggest that an important problem in the War on Poverty lay in its discourse. He assumes that language plays a central role in the formulation of social policy by shaping the context within which people view the social worl.
Chronology -- Rhetoric and public policy: the force of symbolic choice -- Inception: the war is declared -- Rhetorical crisis: the transformation of the military objective -- Rhetorical crisis: the transformation of the enemy -- Rhetorical crisis: the transformation of weapons and tactics -- Consummation: the stalemated war -- The impasse of the liberal argument.
Includes bibliographical references (pages 256-266) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Johnson, Lyndon B; Economic assistance, Domestic -- United States; United States -- Politics and government -- 1963-1969.; États-Unis -- Politique et gouvernement -- 1963-1969.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Economic assistance, Domestic; Politics and government; United States; Sozialpolitik; Armut; USA; Geschichte 1964-1968.; Geschichte (1963-1969); 1963-1969; Electronic book